Regulation of Effector Treg Cells in Murine Lupus. Issue 6 (26th May 2016) - Chandrasekaran, Uma; Yi, Woelsung; Gupta, Sanjay; Weng, Chien‐Huan; Giannopoulou, Eugenia; Chinenov, Yurii; Jessberger, Rolf; Weaver, Casey T.; Bhagat, Govind; Pernis, Alessandra B.
Abstract : Objective: Treg cells need to acquire an effector phenotype to function in settings of inflammation. Whether effector Treg cells can limit disease severity in lupus is unknown. Interferon regulatory factor 4 (IRF‐4) is an essential controller of effector Treg cells and regulates their ability to express interleukin‐10 (IL‐10). In non–Treg cells, IRF‐4 activity is modulated by interactions with DEF‐6 and its homolog switch‐associated protein 70 (SWAP‐70). Although mice lacking both DEF‐6 and SWAP‐70 (double‐knockout [DKO] mice) develop lupus, they display normal survival, suggesting that in DKO mice, Treg cells can moderate disease development. The purpose of this study was to investigate whether Treg cells from DKO mice have an increased capacity to become effector Treg cells due to the ability of DEF‐6 and SWAP‐70 to restrain IRF‐4 activity. Methods: Treg cells were evaluated by fluorescence‐activated cell sorting. The B lymphocyte–induced maturation protein 1 (BLIMP‐1)/IL‐10 axis was assessed by crossing DKO mice with BLIMP‐1‐YFP‐10BiT dual‐reporter mice. Deletion of IRF‐4 in Treg cells from DKO mice was achieved by generating FoxP3 Cre IRF‐4 fl/fl DKO mice. Results: The concomitant absence of DEF‐6 and SWAP‐70 led to increased numbers of Treg cells, which acquired an effector phenotype in a cell‐intrinsic manner. In addition, Treg cells from DKO mice exhibited enhanced expression of the BLIMP‐1/IL‐10 axis. Notably, DKO effector Treg cells survived and expanded as disease progressed. The accumulation of Treg cells from DKO mice was associated with the up‐regulation of genes controlling autophagy. IRF‐4 was required for the expansion and function of effector Treg cells from DKO mice. Conclusion: This study revealed the existence of mechanisms that, by acting on IRF‐4, can fine‐tune the function and survival of effector Treg cells in lupus. These findings suggest that the existence of a powerful effector Treg cell compartment that successfully survives in an unfavorable inflammatory environment could limit disease development.